2014
DOI: 10.1371/journal.pone.0114727
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Tiered Service Delivery Model (ITSDM) Based on Local CD4 Testing Demands Can Improve Turn-Around Times and Save Costs whilst Ensuring Accessible and Scalable CD4 Services across a National Programme

Abstract: BackgroundThe South African National Health Laboratory Service (NHLS) responded to HIV treatment initiatives with two-tiered CD4 laboratory services in 2004. Increasing programmatic burden, as more patients access anti-retroviral therapy (ART), has demanded extending CD4 services to meet increasing clinical needs. The aim of this study was to review existing services and develop a service-model that integrated laboratory-based and point-of-care testing (POCT), to extend national coverage, improve local turn-ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
129
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(135 citation statements)
references
References 15 publications
5
129
0
Order By: Relevance
“…1 This confirms the decentralisation of CD4 test requests. Additionally, 14 health districts in South Africa do not have a local in-district CD4 services.…”
Section: Introductionsupporting
confidence: 65%
See 1 more Smart Citation
“…1 This confirms the decentralisation of CD4 test requests. Additionally, 14 health districts in South Africa do not have a local in-district CD4 services.…”
Section: Introductionsupporting
confidence: 65%
“…1 Additionally, 11 Tier 3 laboratories were proposed. For this scenario, testing would be retained at 30 of the existing CD4 laboratories.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the Xpert VL assay performance in this study, suggested placement within the proposed South African tiered (also known as level of service facility) laboratory framework could be as follows [3]: Tier 5 could continue to provide high volume, centralized plasma-based testing in reference facilities with current platforms such as Roche and Abbott, with expansion of plasma testing to tier 4 and tier 3 using GeneXpert 48/80/16/4 instruments that are currently placed at regional and district level laboratories and where technical and implementation experience is already in place with this technology. Critical to this potential future implementation, however, is still the analysis of throughput and current GeneXpert utility if this platform is to be optimised for polyvalent testing.…”
Section: Discussionmentioning
confidence: 99%
“…South Africa has used VL testing preferentially for monitoring of ART since program inception, which, is now also strongly recommended by the World Health Organisation (WHO) [2]. There are currently over 3900 National Department of Health (NDoH) clinics providing ART initiation and monitoring services in South Africa [3]. All VL testing requirements to service these clinics is performed and managed by the National Health Laboratory service (NHLS) with oversight from the National Priority Programme (NPP), through 16 centralised VL laboratories across the 9 provinces.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation